Reactive Oxygen Species in Human Biological Systems and Their Reactivity to Oxidative Stress - Aflah, Muhammad Naufal; Maysha, Decintya Jaya; Setyaningrum, Savitri; Yabansabra, Alexander; Azzahra, Uzwathul Fathiha; Fendiyanto, Miftahul Huda; Pratami, Mentari Putri (MUNISI: Military Mathematics and Natural Sciences, 2024)
Aerobic organisms in carrying out their metabolism can result in biological oxidation which produces 2.5% reactive oxygen species (ROS) based on the amount of oxygen supply. Several types of stressors or factors that trigger increased oxidative stress can be caused by physical agents such as the impact of UV radiation and X-rays, non-physiological oxygen levels, drugs, chemical compounds, aging, and pollutants that can cause homeostatic disturbances in cells, survival, and processes—cell signaling. In order to maintain life, cells also have a response to oxidative stress through antioxidant-forming tools in the body such as catalase (CAT), hydroperosidase (HPx), and superoxide dismutase (SOD). If the reactive oxygen species (ROS) produced by the body exceeds the limit of the amount of antioxidants produced by the body, it will cause cells in the body to experience oxidative stress. If the amount of reactive oxygen species (ROS) produced is equivalent to the amount of antioxidants, it will direct cells to growth. This reactive oxygen species (ROS) originates from biological oxidation reactions that occur in the mitochondrial matrix. Thus, neutralizing reactive oxygen species (ROS) in the body can only be suppressed by the reaction of two ROS simultaneously, so that two electrons that were initially unpaired will become paired through both enzymatic and non-enzymatic antioxidants and additional antioxidants needed by the body.